Discovery of sertraline and its derivatives able to combat drug-resistant gastric cancer cell via inducing apoptosis. (1st June 2021) - Mu, Chao; Peng, Rui-Kun; Guo, Chun-Ling; Li, Ao; Yang, Xiu-Ming; Zeng, Rong; Li, Yu-Long; Gu, Jing; Ouyang, Qin
Graphical abstract: Abstract: Resistance phenomena during chemotherapy of tumor has been severely hampering the applications of chemotherapeutics. Due to advantage of drug repurposing, discovery of new chemosensitizers based on approved drugs is an effect strategy to find new candidates. Herein, we found antidepressant drug – sertraline, could sensitize drug-resistant gastric cancer cell (SGC-7901/DDP) with the IC50 value of 18.73 μM. To understand the structure–activity relationship and improve the activity, 30 derivatives were synthesized and evaluated. The IC50 value of the best compound was improved to 5.2 μM. Moreover, we found apoptosis induction and cell cycle arrest was the reason for the cell death of the drug-resistant cells after treatment of sertraline and derivatives, and PI3K/Akt/mTOR pathway was involved.